If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2a + 3b = 6c Solving 2a + 3b = 6c Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3b' to each side of the equation. 2a + 3b + -3b = -3b + 6c Combine like terms: 3b + -3b = 0 2a + 0 = -3b + 6c 2a = -3b + 6c Divide each side by '2'. a = -1.5b + 3c Simplifying a = -1.5b + 3c
| -3(3c+15)-(10+c)=35 | | 170=c+146 | | 140-6x=21x+17 | | (8x^3-2x^2-4x+7)-(6x^2+8)=0 | | 6t^2-24t=0 | | -n/2.5-7=-82 | | 6+x=13 | | m/6=-4 | | 6t^2-42t=0 | | 1+(1/3)+(1/9) | | 7t^2+42t=0 | | 15/7y=3 | | -5(6p+4)-2p=-32p+14 | | s^2=36-5s | | (15/57) | | c/2=7 | | 3x+4(x+5)=34 | | 2ln(x)=ln(4x+6)-ln(2) | | (1/4)+(1/7)+(1/12) | | 2(4x+5)-10=4(2x-3)12 | | 6x+5y=1164 | | 2x+10y=22 | | 16=10/3a | | 2/x+1-1/x-2=-1/2 | | -3x+5(x-5)=75 | | 2x^2-5+55=0 | | (7-2k)+3(5-3k)=k+8 | | 1/5x+13+x=-1/10(x-40)+4 | | 7-8x=79-22x | | 7-8=79-22x | | 3x-8=6x+5 | | 6x-3=4x+-2 |